The great space between: a service station nexus in the Soutpansberg - James, Alistair (My University, 2016)
This thesis aims to study the idea of non-place; a point on the line between a beginning and an end. My site is in the Soutpansberg mountain range in the Limpopo province. There is a rich history of movement in the area, from ancient trade routes, to central African migration, the Voortrekkers, the British ideal of a Great North Road, apartheid homelands and currently, the Zimbabwean diaspora. All of these stages are examples of flux, movement, non-place… I have aimed to take a history of the area and apply its relevance to a scarred landscape that is bisected by the N1 highway. Perhaps turning a non-place into a place; perhaps just giving a non-place some relevance. By placing a large service station, a market and a place to sleep onto this site, I wish to revive what it has always been: a movement route, a point on the line; and once again bring to the Great North Road, something so general and banal, yet something fundamentally etched with its DNA. A place en route in the great space between.
Keywords: City planning--South Africa; Space (Architecture); Landscape; Soutpansberg (South Africa)